The Appearance of Dural Sealants under MR Imaging - Tarapore, P.E.; Mukherjee, P.; Mummaneni, P.V.; Ames, C.P. (American Journal of Neuroradiology, 2012)
Dural sealants are an adjunct to obtain watertight closure after intradural procedures. This study aims to characterize the appearance on MR imaging of 3 commonly employed dural sealants: fibrin glue, PEGH, and BSAG. To this end, patients who underwent spinal intradural procedures that included the use of dural sealant during closure were identified retrospectively. Post-operative data on 15 patients, including complications such as pseudomeningocele formation and infection, were gathered. The appearance of dural sealants on follow-up MR imaging scans within 3 days of surgery was analyzed. Fifteen patients were identified (5 with fibrin glue, 5 with PEGH, and 5 with BSAG applied during closure) with appropriately timed post-operative MR imaging scans. All 3 substances were identifiable based on anatomic location and imaging characteristics on post-operative MR imaging in standard T1, T1 PGFS, and T2 FSE. Definite differentiation between CSF and fibrin glue or PEGH was not possible with the T1 or T1 PGFS, or with the T2 FSE. Differences in intensity between CSF and BSAG were also not significant on either T1 sequence, but they were statistically significant on the T2 FSE. All patients had an uneventful post-operative course, and no patients developed post-operative pseudomeningocele at 30 days. This study concludes that water-based dural sealants such as fibrin glue and PEGH are difficult to differentiate from CSF on standard T1, T1 PGFS and T2 FSE, while BSAG is easily recognized on the T2 FSE. Recognition of water-based sealants therefore requires communication between the neurosurgeon and the neuroradiologist to avoid post-operative misidentification. BSAGbovine serum albumin and gluteraldehyde polymerFSEfast spin- echoPEGHpolyethylene glycol hydrogelPGFSpostgadolinium fat saturation